Filip Istner (1912–1990) - Famulska-Ciesielska, Karolina (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2012)
Filip Istner was a poet and a press and radio journalist. Until 1957 he worked for the Polish Radio, and after that as a freelancer in Kurier Polski and Tygodnik Powszechny. After leaving Poland he wrote for Kultura in Paris and Wiadomości in London. In 1962—as Wiktor Nowicz— he published a book “Watykan w poszukiwaniu nowych dróg.” He left Poland in December of the year 1968—together with his wife and 12-year-old daughter and moved to Israel. After his wife’s death he moved to Sweden. He published only one tome of poetry in Stockholm titled “To już.” Many of the poems remained handwritten. Istners’ poetical debut is an expression of mature, late creativity. Czesław Miłosz compared Istner’s poetry to the poetry of Aleksander Wat. Filip Istner’s poetry is evidence of a huge sensitivity both moral and spiritual. F. Istner’s archive can be found in the Archives of Polish Emigration in Toruń.